Vaginal Cleansing and Post-Cesarean Infectious Morbidity? Updated Systematic Review and Meta-Analysis of Randomized Trials - Marco La Verde; Marco Torella; Irene Iavarone; Rossella Molitierno; Antonio Cerillo; Margherita Casillo; Maria Maddalena Marrapodi; Mario Fordellone; Liliana Mariani; Chiara Melito; Barbara Gardella; Mattia Dominoni (Biomedicines)
Background: Endometritis, maternal fever and wound infection represent the most frequent post-cesarean complications. The aim of the present research was to evaluate the incidence of post-cesarean infections after vaginal cleansing. Materials and methods: The databases analyzed were MEDLINE, Scopus, EMBASE, CENTRAL, Google Scholar, Clinicaltrials.gov and the Register of Controlled Trials. No language or geographical restrictions were applied. We included only randomized controlled trials that analyzed various vaginal antiseptic solutions to reduce postpartum endometritis. The terms employed were as follows: vaginal solution, cesarean section, endometritis, wound infection, chlorhexidine, povidone, metronidazole, cetrimide, and pregnancy. The PICO categorization was as follows: P—population: pregnant women; I—intervention: vaginal antiseptic; C—control: hands-off or routine care; O—outcome: post-cesarean endometritis, wound infection and postoperative fever; S—study design: randomized controlled trials. Results: A total of 32 articles, including 13,853 participants, were selected. The vaginal cleansing group showed a low incidence of endometritis. The chlorhexidine group had an OR of 0.56 (95% CI 0.45–0.70, p = 0.010). The povidone group had an OR of 0.47 (95% CI 0.37–0.59, p = 0.002). Considering maternal fever, 2598 patients from 5 studies in the chlorhexidine group were analyzed, alongside 6965 patients from 18 trials in the povidone group. The povidone group presented an Odds ratio of 0.47 (95% CI 0.38–0.57, p = 0.0001). A reduction in wound infection incidence was observed in the povidone group (OR = 0.59, 95% CI = 0.42–0.82, p < 0.05). Conclusions: Vaginal cleansing before cesarean section, particularly with povidone solutions, reduces the incidence of postoperative endometritis and maternal fever.